Evaluation of fatigue crack propagation behavior of 316LN TIG weldments at liquid helium temperature. (September 2020) - Huang, Chuanjun; Xin, Jijun; Zhang, Hengcheng; Wei, Jing; Huang, Rongjin; Xu, Dong; Song, Yuntao; Li, Laifeng
Highlights: Fatigue crack propagation behavior of 316LN tungsten inert gas (TIG) weldment and weldment with post weld heat treatment (PWHT) was investigated at liquid helium temperature. Weldment with PWHT results in the highest fatigue crack propagation resistance, whereas the base material demonstrates the lowest fatigue crack propagation resistance. The crack featured with a transgranular propagation characteristics for the base material, the weldments without and with PWHT. More amount of strain-induced martensite near the crack tip in the base material compared to in the as-welded weldment and in the weldment with PWHT. The strain-induced martensite transformation plays a crucial role in determining the fatigue crack propagation behavior at cryogenic temperature. Abstract: In the present work, fatigue crack propagation behavior of 316LN tungsten inert gas (TIG) weldment and weldment with post weld heat treatment (PWHT) was investigated at liquid helium temperature. Results indicates that the weldment with PWHT results in the highest fatigue crack propagation resistance, whereas the base material demonstrates the lowest fatigue crack propagation resistance. Microstructure evolution reveals that the fatigue crack propagation is characterized as transgranular fracture for the base material as well as the as-welded weldments and the weldment with PWHT. Moreover, the crack propagation path of the weldments shows a zigzag crack extension, especially for the weldment with PWHT, whereas the crack extension of the base material is relative straight. Electron backscattered diffraction reveals more amount of strain-induced martensite near the crack tip in the base material compared to in the as-welded weldment and in the weldment with PWHT, which is considered to be a crucial factor in the fatigue crack propagation behavior at cryogenic temperature.